Asphericity of a length four relative presentation - Bin Ahmad, Abd Ghafur; Al-Mulla, Muna A.; Edjvet, Martin (World Scientific, 2016)
We consider the relative group presentation P = < G, X | R > where X = { x \} and R = { xg_1 xg_2 xg_3 x^{-1} g_4 }. We show modulo a small number of exceptional cases exactly when P is aspherical. If the subgroup H of G is given by H = < g_1^{-1} g_2, g_1^{-1} g_3 g_1 , g_4 > then the exceptional cases occur when H is isomorphic to one of C_5,C_6,C_8 or C_2 X C_4.